0940 Polysomnographic Sleep Predicts PTSD Arousal Symptoms in Civilian and Veteran Young Adults. (27th April 2018) - Brownlow, J A; Barilla, H; Gehrman, P; Ross, R J; Kling, M A; Bhatnagar, S; Mellman, T A
Abstract: Introduction: Insomnia is prevalent in PTSD, and is one of the arousal and reactivity cluster symptoms. Many of the polysomnographic (PSG) findings in PTSD relate to rapid eye movement (REM) sleep, which, relative to other sleep stages, is a state of increased central nervous system arousal. Little is known about the relation between REM sleep measures and the arousal symptom cluster in PTSD. The purpose of this study was to determine relationships of PSG measures with PTSD arousal symptoms in civilian and veteran young adults, and to determine which sleep variables were predictive of PTSD arousal symptoms. Methods: Seventy-one subjects (40.8% female; mean age 27.39, SD=9.69) were included. The civilians (n=44) were from a study focused on PTSD, sleep, and nocturnal blood pressure, and the veterans (n=27) were from a study focused on neurobiological factors related to hyperarousal in PTSD. Subjects underwent two nights of PSG. Sleep continuity (TST, SE, WASO, SL), sleep architecture (Stages N1, N2, N3, and REM sleep), and REM sleep variables (REM latency, number of REM segments) were assessed. The arousal PTSD symptom cluster was assessed using the Clinician-Administered PTSD scale. Results: With the exception of SL, all sleep continuity (r's=-.370-.247, p's<.05), sleep architecture (r's=-.553-.678, p's<.05), and REM sleep variables (r's=-.418-.284, p's <.05) were associated with PTSD arousal symptoms. Sleep architecture variables predicted PTSD arousal symptoms (R 2 =.505, F=16.85, p<.001), specifically Stage N1 sleep (t=3.79, p<.001) predicted PTSD arousal symptoms independently of Stages N2, N3, and REM sleep. REM sleep variables predicted PTSD arousal symptoms (R 2 =.190, F=7.991, p=.001), specifically, the number of REM segments (t=-3.03, p=.003) predicted PTSD arousal symptoms independently of REM latency. Conclusion: These data provide evidence for a relationship between REM sleep measures and PTSD arousal symptoms. Arousal mechanisms active during REM sleep may also participate in the cluster of PTSD arousal symptoms. Neural processes active during Stage N1 sleep may also play a role in PTSD hyperarousal. Support (If Any): Funded by Defense Advanced Research Projects Agency, US Army Research Office (grant W911NF1010093) and NIH grants HL087995-01A2S1 and UL1TR000101.